Degrowth enthusiasm and the transformation blues of the East: Reflections on integrating post-socialist transformation experiences into the degrowth discourse - Jana Gebauer; Gerrit von Jorck; Lilian Pungas (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2023)
This paper traces the links between post-socialist transformations and the degrowth movement. Based on a series of workshops entitled "Degrowth Enthusiasm and the Eastern Blues" that we organised in recent years, this paper focuses on the following questions: what can we learn from the state-socialist societies' transformation processes into capitalist societies? What experiences and practices before and after these transformations can potential degrowth societies build on? To what extent can people's experiences with an alternative system and its transformation contribute to unfolding their potential in a social-ecological transformation and to overcoming 'change fatigue'? We present key findings from our workshops, which we combined with our own empirical evidence from Estonia and a theoretical examination of (post-)socialist economics to form six theses that we consider essential for a decolonial degrowth debate.
Keywords: O44; P28; P30; P31; Q01; Q12; 330; degrowth; social-ecological transformation; post-socialist transformation; subsistence farming